“Uma coisa que nunca imaginei na nossa vida”: a vivência das famílias não doadoras frente à morte encefálica - Rossato, Gabriela Camponogara (2017)
Currently, the number of dead donor organ transplants in Brazil has increased yearly. Based on data from the Health Ministry, in the last ten years, from 2004 to 2014, the number of transplants conducted in Brazil increased 63,8% concerning effective donors. Thus, mentioning organ donation is talking about an important subject for families that donate (or do not donate) organs and those that receive them, because they are directly related to this process since they decide about donating or not. For the donation to happen, the patient must receive a brain death diagnosis, which corresponds to a person’s effective death. In this context, death generates implications for the family in terms of reactions and adjustments in relation to the experience. The purpose of the study is to understand the experience of non-donor families before brain death. The analysis is descriptive, qualitative and has the Symbolic Interactionism as its theoretical background. The place of the study was the Adult Intensive Care Unit (AICU) of the University Hospital of Santa Maria (UHSM). The participants of the study were families who had their members diagnosed with brain death and denied organ donation, with a time variation from two years to 15 days concerning this experience. The total number of interviewed family members was 11, totalizing 6 families. Data collection was carried out from April to November in 2016, through a narrative interview. Data analysis was carried out through the narrative regarding the formation of categories with content emphasis. The Resolution 466/12 was respected and data collection began only after the project approval by the research ethics committee. Through data analysis, the following topics and sub-topics emerged. Topic 1: Uncertainty of what may happen, which comprised the sub-topics: An unknown and unexpected situation, The hope and The decision of not donating. Such topics highlight that families experience an unknown and unexpected situation, considering it difficult, shocking and sad as well. Along with families, hope is present from the very moment of the accident until the decision of not donating. Topic 2: Knowing that there is no turning back: from brain death confirmation to death as a fait accompli, which comprised the sub-topics: Removal of life support and “They called us to fetch the body”: Death itself, which proves that families suffer with the loss and emotional distress is visible either because of the removal of life support or the waiting time for the body, showing that the loss generates a reaction in each family member and that family and unknown people’s support is essential to face brain death and organ donation process. Hence, is was possible to understand that non-organ donor families’ experience before brain death as something they have never imagined to go through.